MANFAAT HYPNOBIRTHING DAN DIFUSE AROMATHERAPY LAVENDER TERHADAP LAMA PERSALINAN KALA I DAN II - Durrotun Munafiah; Nur Laila; Tri Ismu Pujiyanto; Sa'adah Mujahidah; Mariza Mustika Dewi (Midwifery Care Journal, 2022)
The prolonged first and second stage of labor will cause various maternal and fetal complications. Methods for mothers to feel relaxed is the hypnobirthing relaxation method and using Lavender Aromatherapy. The aim of the study was to determine the effect of the combination of hypnobirthing and diffuse lavender aromatherapy on the duration of labor in the I and II stages. This type of research is quantitative, quasi-experimental design with posttest only control group design. The population of this study was all mothers giving birth in the Tengaran Health Center Work Area in August 2021 with a total of 20 respondents. The sample is set at 10 respondents per group. The sampling technique in this research is purposive sampling. Data analysis used univariate and bivariate analysis using independent t-test and Mann Whitney. The duration of the first stage of labor in the group that gave the combination of hypnobirthing and diffuse lavender aromatherapy had an average length of the first stage of 289.5 minutes, the median of 290 minutes, the average length of the second stage of 29 minutes, and the median of 30 minutes. The control group had an average length of the first stage of 330 minutes, a median of 340 minutes, an average length of the second stage of 38.5 minutes, a median of 40 minutes. There is an effect of the combination of hypnobirthing and diffuse aromatherapy lavender on the duration of labor in the first and second stages (0.0010.05 and 0.0060.05).